Realizing Excellent and Quality Public Policy through Emergency Call 112 Service in Probolinggo City - Lailatul Fitria, Nurul Jannah; Marwiyah, Siti; Busthomy, Ach. Noor (International Publisher (YAPENBI), 2023)
Policy challenges include conflicts with other regulations, inconsistencies, multiple interpretations, and inoperability, along with lack of evidence. Public policy is related to decisions in allocating resources in order to utilize and provide benefits to society with the intervention of leaders and policy analysis. The policy that needs to be considered is the government's readiness policy in assisting and saving the community in urgency and emergency conditions. It is applied to NTPD 112 in Probolinggo City. This attracts the author to conduct research related to NTPD 112 which is aligned with the principles of public policy. This research is a descriptive qualitative research to examine the concept of excellent and quality public policy with a pilot call 112 service in Probolinggo City. Data and information were collected through interviews, observations, and literature studies. The Probolinggo City Government has formulated public policies on 112 emergency call services with the main principles of excellent policies, including policies for the public; irrevocable policies; great and good policies; policies with management; policies with moral values; policies with systems; policies are a gift to the community; policies are an honor; policies to glorify the community; and policies as learning.